An experimental and computational investigations of supramolecular anion–π/π–π/π–anion assemblies in mononuclear Zn(II) complexes with a versatile tetradentate N-donor Schiff base ligand. (14th December 2015) - Roy, Mainak; Bauzá, Antonio; Frontera, Antonio; Banerjee, Saikat; Halder, Sattwick; Saha, Amrita
Graphical abstract: Three zinc(II) complexes, [Zn(L)(Cl)]ClO4 (1 ), [Zn(L)(Br)]ClO4 (2 ) and [Zn(L)(N3 )]ClO4 (3 ), (L = N, N′-bis-(1-pyridin-2-yl-ethylidene)-propane-1, 3-diamine) have been synthesized and characterized using different spectroscopic techniques including X-ray crystallography. In the three complexes, interesting anion–π/π–π/π–anion assemblies are formed in the solid state. The contribution of each interaction to the formation of the assembly has been computed using several theoretical models and density functional theory (DFT) calculations. Abstract: Three newly synthesized zinc(II) complexes, [Zn(L)(Cl)]ClO4 (1 ), [Zn(L)(Br)]ClO4 (2 ) and [Zn(L)(N3 )]ClO4 (3 ), have been obtained from a tetradentate symmetrical Schiff base, N, N′-bis-(1-pyridin-2-yl-ethylidene)-propane-1, 3-diamine (L). All complexes have been characterized using different spectroscopic techniques including X-ray crystallography. In the three complexes, interesting anion–π/π–π/π–anion assemblies are formed in the solid state. The contribution of each interaction to the formation of the assembly has been computed using several theoretical models and density functional theory (DFT) calculations. The mutual influence of anion–π and π–π interactions has been also analyzed and a reinforcement of both interactions is demonstrated. This theoretical study is certainly important to shed light into the delicate mechanism that governs the molecular recognition and crystal packing.